THE ETHICAL AND AESTHETICAL DIMENSION OF FIGURATIVE CLASSICAL CALLIGRAPHY PAINTING - Dini Kurniawati (Teosofia: Indonesian Journal of Islamic Mysticism, 2016)
The current phenomenon indicates that the use of the term of art experienced a shift in meaning, which is arbitrary. Art is only seen as an expression of free expression, without care about the meaning contained in the work of art. However, it is not evident among Moslem artists in expressing their work in figurative calligraphy painting. Although in Islam, painting especially in paint the creature living (figure) got a bad response, but the Moslem artists were able to present works that are not only beautiful but also the messages. The research questions in this thesis are first what is the ethical and aesthetical message of figurative calligraphy painting? And  is there a  relationship between ethical and aesthetical messages in figurative calligraphy painting? Trough  an interpretative qualitative and a symbolic interaction approach. The research concluded that the ethical messages are Posts contain praying  illustrated in the form of ‘abid in praying. It contains the meaning that human is weak creature and always does wrong. Therefore, humans need forgiveness from Allah. Posts of Ali Ibn Abi Thalib was illustrated in the form of lion. It describes and contains the meaning of braveness and heroism of Ali in defense of Allah religion. The aesthetical message in every figurative calligraphy painting is a manifestation of the beauty that exists in the universe. Figurative calligraphy painting is described the Majesty, Power and Oneness of Allah, the art was created is the manifestation of tawḥid